Self-acceptance in the extraordinary life of Sam Hell novel by Robert Dugoni - Tiana Aulia (Morphosis: Journal of Literature, 2024)
The aim of this study is to analyze the self-acceptance experienced by the main character in the novel The Extraordinary Life of Sam Hell (2018) by Robert Dugoni. This study applies qualitative research methods as the analysis is presented in the form of text. To guide this study, the writer uses Elizabeth Hurlock’s (1974) theory of self-acceptance. This analysis results in the process and representation of self-acceptance. Experiencing rejection in life due to different conditions does not necessarily make individuals give up on their lives and reject themselves. The way main character portrays self-acceptance is by understanding and appreciating himself. There are several factors of self-acceptance that set the background of an individual’s life journey and make him learn what aspects can be developed to achieve goals in his life. After successfully understanding and accepting himself, he successfully lives the happy life he wants, he is free from negative feelings and forgives past events. Keywords: Self-Acceptance, Rejection, Self-Understanding